A STUDY ON COLLABOURATION WITHIN THE SUPPLY CHAINS OF CORPORATE RETAILERS IN KERALA - Biju M.K. and Faisal U (ACADEMICIA: An International Multidisciplinary Research Journal, 2013)
There are corporate retail chains are present in Kerala almost for a decade with the entry of Margin Free Markets. Now, many of the leading corporate retailers are have their presence in the state. The success of a large retail lies in the proper management of its supply chain which, in turn, is the management of upstream and downstream relationships with and customers to deliver superior customer value at less cost to the supply chain as a whole. The relationship and collaboration with the other entities in the supply chain is crucial. This study is aimed at collecting the opinions of retailers and transporters about the suppliers in the supply chain to identify the gaps between the expectations and performances. The study was descriptive using primary data collected through administering two questionnaires. Multi stage sampling was used to collect the samples with sizes of 126 and 28 for retailers and transporters respectively. The hypotheses were tested using statistical tests. It was found that Big Bazaar is most satified with the suppliers and Others category is least satisfied. It was also found that there is a huge gap existing between expectations of the transporters and the performance of the suppliers. Overall, the retilaers and transporters are not satisfied with the suppliers. Lots of aspects where the suppliers need to improve are suggested along with suggestions separatley made for each retail chain. Theare are other suggetions on application of latetst tools available in supply chain management.